2005
DOI: 10.1161/01.cir.0000165066.71481.8e
|View full text |Cite
|
Sign up to set email alerts
|

Postinfarction Gene Therapy Against Transforming Growth Factor-β Signal Modulates Infarct Tissue Dynamics and Attenuates Left Ventricular Remodeling and Heart Failure

Abstract: Background— Fibrosis and progressive failure are prominent pathophysiological features of hearts after myocardial infarction (MI). We examined the effects of inhibiting transforming growth factor-β (TGF-β) signaling on post-MI cardiac fibrosis and ventricular remodeling and function. Methods and Results— MI was induced in mice by left coronary artery ligation. An adenovirus harboring soluble TGF-β type II recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 41 publications
5
142
0
1
Order By: Relevance
“…Recently, Peterson 14 showed that both cardiac hypertrophy and fibrosis in heart failure are characterized by an elevated level of circulating TGF-b and Fedulov et al 15 showed a strong positive correlation between serum TGF-b and cardiac fibrosis. Okada 16 has also recently shown that gene therapy directed against TGF-b attenuates left ventricular remodeling and heart failure, after a myocardial infarction, in a time-dependent manner. Angiotensin (1À7) prevent heart dysfunction and left ventricular remodeling Y Li et al…”
Section: Angiotensin (1à7) Prevent Heart Dysfunction and Left Ventricmentioning
confidence: 98%
“…Recently, Peterson 14 showed that both cardiac hypertrophy and fibrosis in heart failure are characterized by an elevated level of circulating TGF-b and Fedulov et al 15 showed a strong positive correlation between serum TGF-b and cardiac fibrosis. Okada 16 has also recently shown that gene therapy directed against TGF-b attenuates left ventricular remodeling and heart failure, after a myocardial infarction, in a time-dependent manner. Angiotensin (1À7) prevent heart dysfunction and left ventricular remodeling Y Li et al…”
Section: Angiotensin (1à7) Prevent Heart Dysfunction and Left Ventricmentioning
confidence: 98%
“…Two recent studies showed that inhibition of TGF-β signaling by injection of an adenovirus harboring soluble TGF-β type II receptor in the hindlimb muscles resulted in attenuated left ventricular remodeling by modulating cardiac fibrosis [318], [319]. However, early TGF-β inhibition significantly increased mortality and exacerbated left ventricular dilation enhancing cytokine synthesis, suggesting that during the phase of resolution of the inflammatory response, TGF-β signaling plays an important role in suppression of inflammatory mediator synthesis [318].…”
Section: The Role Of Tgf-β In Myocardial Infarctionmentioning
confidence: 99%
“…In a model of non-reperfused infarction, TGF-β inhibition through administration of a neutralizing antibody had detrimental effects, accentuating chamber dilation, increasing myocardial MMP expression, and reducing collagen synthesis (84). Two independent investigations inhibiting TGF-β by using gene transfer of the extracellular domain of TβRII suggested that TGF-β may play a key role in fibrosis of the infarcted heart (63,85). TGF-β inhibition after the inflammatory phase of cardiac repair attenuated deposition of fibrous tissue in the infarcted region (85).…”
Section: Tgf-β In Regulation Of Fibroblast Phenotype and Functionmentioning
confidence: 99%